1985
DOI: 10.1193/1.1585307
|View full text |Cite
|
Sign up to set email alerts
|

The Borah Peak, Idaho Earthquake of October 28, 1983—Buildings and Schools

Abstract: At 8:07 AM MDT, October 28, 1983, a major earthquake (Ms = 7.3) rocked central Idaho. The earthquake source zone was near the base of Mt. Borah with an elevation of 12,662 ft (3859 m). This earthquake is the largest earthquake to occur in Idaho in recorded history, and is the strongest to occur in the continental United States since the magnitude 7.1 Hebgen Lake Montana earthquake of 1959. It was felt that a study of the effects of such a large magnitude earthquake on buildings and communities would enhance un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The performance of such buildings is extensively documented in published reconnaissance reports (Scholl and Stratta 1984;Shah et al 1984;Reitherman et al 1984;Kariotis 1984;Adham 1985;Reitherman 1985;Swan et al 1985;Esteva 1988;Hart et al 1988;Deppe 1988;Moore et al 1988;Muria-Vila and Meli 1989;Meli 1989;"Armenia" 1989;Mitchell et al 1989;"Loma" 1990;Bruneau 1990;Cross and Jones 1991;Rutherford and Chekene 1991;Kariotis et al 1991) from which a number of observations are possible. Generally 9 With the exception of a comprehensive data collection by Rutherford and Chekene (1991) and a few other reports, damage surveys reported in the literature tend to concentrate on the downtown cores where the building stock consists mostly of older URM buildings, and may thus be biased toward higher damage (Shah et al 1984).…”
Section: General Modes Of Failure Of Urm Buildings During Earthquakesmentioning
confidence: 99%
“…The performance of such buildings is extensively documented in published reconnaissance reports (Scholl and Stratta 1984;Shah et al 1984;Reitherman et al 1984;Kariotis 1984;Adham 1985;Reitherman 1985;Swan et al 1985;Esteva 1988;Hart et al 1988;Deppe 1988;Moore et al 1988;Muria-Vila and Meli 1989;Meli 1989;"Armenia" 1989;Mitchell et al 1989;"Loma" 1990;Bruneau 1990;Cross and Jones 1991;Rutherford and Chekene 1991;Kariotis et al 1991) from which a number of observations are possible. Generally 9 With the exception of a comprehensive data collection by Rutherford and Chekene (1991) and a few other reports, damage surveys reported in the literature tend to concentrate on the downtown cores where the building stock consists mostly of older URM buildings, and may thus be biased toward higher damage (Shah et al 1984).…”
Section: General Modes Of Failure Of Urm Buildings During Earthquakesmentioning
confidence: 99%
“…Although not part of the load bearing structure, their significance stems from the survivability requirement in the aftermath of a seismic event and their vast contribution to the overall construction costs [1]. Nevertheless, past earthquakes have demonstrated that current methods for the seismic analysis of secondary substructures lack the necessary rigour and robustness, resulting in expensive and often unreliable solutions [2,3,4,5].…”
Section: Introductionmentioning
confidence: 99%